Anti-blue light optical protective film and preparation method thereof
By using blue light absorbers prepared by materials such as graphene quantum dots, combined with polyvinyl alcohol and ultrapure water, an anti-blue optical protective film is prepared, which solves the problem that the existing technology is difficult to effectively block harmful blue light, while maintaining high light transmittance, achieving The possibility of industrial production.
Patent Information
- Application Number
- CN202411815533.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Existing blue light-proof technology is difficult to effectively block harmful blue light, while maintaining high light transmittance in visible light areas, and is difficult to produce in industrialized production.
Blue light composed of graphene quantum dots, anhydrous ethanol, aminonitrobenzene compounds, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide The absorbent is prepared by hydrothermal reaction and amide reaction, combined with the mixture of polyvinyl alcohol and ultrapure water to prepare an anti-blue optical protective film.
It realizes effective absorption of harmful blue light without changing the visible light area of the optical film, and has a good blue light blocking effect.
Smart Images

Figure CN119291831B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of blue light protection optical elements, and in particular relates to a blue light protection optical protective film and a preparation method thereof. Background Art
[0002] With the change of lifestyle and the improvement of working and living conditions, especially the popularization of electronic products and artificial lighting, people are exposed to more blue light than before. However, scientific research results show that high-energy short-wave blue light (400-460 nm) can penetrate the lens directly to the retina, causing myopia. Long-term exposure to blue light will cause visual fatigue and VDT syndrome. At the same time, blue light can inhibit the secretion of melatonin, disturb sleep, and increase the incidence of major diseases. Therefore, it is of great significance to develop an optical protective film that can effectively block blue light.
[0003] The current blue light protection technologies mainly include absorbing blue light, reflecting blue light, limiting blue light by changing the microstructure of the film surface and generating a magnetic field by powering on. Among them, the disadvantages of reflective films are high film cost and high precision of the thickness of the deposited layer; changing the microstructure of the film surface and generating a magnetic field by powering on has the disadvantage of being difficult to industrialize and apply; absorption films are the most widely used, and blue light absorbers are their main part. However, it is also difficult to control the dosage of blue light absorbers and the accurate and precise blue light protection band. It is easy to block beneficial blue light while protecting harmful blue light, causing the color balance to be seriously damaged, thereby reducing the transmittance of the material. In view of this, this solution was created. Summary of the invention
[0004] In view of the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide an anti-blue light optical protective film and a preparation method thereof. When used, the blue light absorber in the anti-blue light optical protective film will not change the high transmittance of the optical film itself in the visible light region, and can also absorb harmful blue light.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: an anti-blue light optical protective film, comprising 0.2-1.4 parts of a blue light absorber, 9-27 parts of ultrapure water and 1-3 parts of polyvinyl alcohol by weight;
[0006] Calculated by weight, the blue light absorber consists of 0.07-0.09 parts of graphene quantum dots, 110-130 parts of anhydrous ethanol, 0.05-0.07 parts of aminonitrobenzene compounds, 1-2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.3-0.6 parts of N-hydroxysuccinimide.
[0007] Furthermore, the concentration of the blue light absorber is 0.1-0.7 wt.%.
[0008] Furthermore, the aminonitrobenzene compounds include 4-nitroaniline, o-nitroaniline and 4-nitro-o-phenylenediamine.
[0009] Furthermore, the blue light absorber is prepared by the following method; comprising the following steps:
[0010] S1, mixing graphene oxide, hydrogen peroxide and ultrapure water, and subjecting the obtained dispersion to a hydrothermal reaction to obtain graphene quantum dots;
[0011] S2, mixing graphene quantum dots, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide and ethanol, and then activating them to obtain a graphene quantum dot reaction solution;
[0012] S3, mixing the graphene quantum dot reaction solution and the aminonitrobenzene compound, and then performing an amide reaction to obtain a blue light absorber.
[0013] Furthermore, the temperature of the hydrothermal reaction in step S1 is 150° C.-180° C., and the insulation time of the hydrothermal reaction is 90-120 minutes.
[0014] Furthermore, the activation temperature in step S2 is room temperature, and the activation time is 1-3 hours.
[0015] Furthermore, in step S3, the temperature of the amide reaction is 30° C.-40° C., and the insulation time of the amide reaction is 22-26 hours.
[0016] A method for preparing a blue light-proof optical protective film comprises the following steps:
[0017] A. mixing polyvinyl alcohol and ultrapure water, and then swelling and dissolving them in sequence to obtain a polyvinyl alcohol solution;
[0018] B. mixing the polyvinyl alcohol solution and the blue light absorber to obtain a mixed material;
[0019] C. Coating the mixed material onto a glass substrate and then drying it to obtain a blue light protection optical protective film.
[0020] Furthermore, the swelling temperature in step A is 20°C-30°C, and the swelling time is 0.5-1 hour; the dissolution temperature in step A is 90°C-110°C, and the dissolution time is 1-3 hours.
[0021] Furthermore, the drying temperature in step C is 60° C.-70° C., and the drying time is 2-4 hours.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention provides an anti-blue light optical protective film and a preparation method thereof. The anti-blue light optical protective film is prepared by using a blue light absorber, wherein the blue light absorber consists of 0.07-0.09 parts of graphene quantum dots, 110-130 parts of anhydrous ethanol, 0.05-0.07 parts of aminonitrobenzene compounds, 1-2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.3-0.6 parts of N-hydroxysuccinimide. When used, the blue light absorber will not change the high light transmittance of the optical film itself in the visible light region, while being able to absorb harmful blue light. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The ultraviolet-visible light absorption spectra of the blue light absorbers in Examples 1-3 of the present invention;
[0025] Figure 2 The ultraviolet visible light transmission spectrum of the anti-blue light optical protective film in Application Examples 1-4 of the present invention;
[0026] Figure 3 The ultraviolet visible light transmission spectrum of the anti-blue light optical protective film in Application Examples 5-8 of the present invention;
[0027] Figure 4 It is the ultraviolet visible light transmission spectrum diagram of the anti-blue light optical protective film in Application Examples 9-12 of the present invention. DETAILED DESCRIPTION
[0028] In order to make the above features and advantages of the present invention more obvious and easy to understand, embodiments are given below with reference to the accompanying drawings for detailed description as follows.
[0029] In this specific embodiment, the room temperature mentioned, unless otherwise specified, means 20° C.-30° C., and will not be repeated in the following.
[0030] The invention provides a blue light absorber. The blue light absorber consists of 0.07-0.09 parts of graphene quantum dots, 110-130 parts of anhydrous ethanol, 0.05-0.07 parts of aminonitrobenzene compounds, 1-2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.3-0.6 parts of N-hydroxysuccinimide in parts by mass.
[0031] The present invention provides a method for preparing a blue light absorber, comprising the following steps:
[0032] S1, mixing graphene oxide, hydrogen peroxide and ultrapure water, and subjecting the obtained dispersion to a hydrothermal reaction to obtain graphene quantum dots (GQDs);
[0033] S2, mixing graphene quantum dots, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide and ethanol, and then activating them to obtain a graphene quantum dot reaction solution;
[0034] S3, mixing the graphene quantum dot reaction solution and the aminonitrobenzene compound, and then performing an amide reaction to obtain a blue light absorber.
[0035] The method for preparing graphene oxide in step S1 comprises the following steps:
[0036] Graphite, sulfuric acid and potassium permanganate are mixed, and low-temperature oxidation, medium-temperature oxidation and high-temperature oxidation are carried out in sequence, and graphene oxide is obtained after cooling.
[0037] Preferably, the graphite is flake graphite powder, and the optimal selection range of the particle size of the graphite is 2000-8000 mesh. Preferably, the concentration of sulfuric acid is 98.3%. Preferably, the mass ratio of graphite to potassium permanganate is 1:6. Preferably, the solid-liquid ratio of graphite to sulfuric acid is 0.02-0.05 g / mL (gram per milliliter).
[0038] The steps of mixing graphite, sulfuric acid and potassium permanganate are as follows: first, graphite and sulfuric acid are mixed to obtain a mixture; then potassium permanganate and the mixture are mixed, and then low-temperature oxidation, medium-temperature oxidation and high-temperature oxidation are carried out in sequence. Preferably, when the mixture and potassium permanganate are mixed, the reaction needs to be carried out in a low-temperature environment to prevent the risk of explosion. The temperature of the low-temperature environment is 0°C-10°C, and the reaction time is 3-5 minutes.
[0039] The best way to mix graphite and sulfuric acid is to stir and mix, the stirring rate is 100-300r / min (revolutions per minute); the time is 3-5 minutes. The best way to mix potassium permanganate and the mixture is to add potassium permanganate to the mixture in batches for mixing; the number of batches is 2-3 times, and the temperature during the batch addition is less than 15 ℃. In order to avoid the risk of explosion of potassium permanganate due to violent oxidation, this scheme adopts the method of controlling the addition rate during the addition of potassium permanganate, and adds potassium permanganate in small amounts and multiple times.
[0040] Preferably, the low-temperature oxidation is carried out in an ice-water bath. The temperature of the low-temperature oxidation is less than 10°C, preferably, the temperature of the low-temperature oxidation is 4°C, and the time of the low-temperature oxidation is 20-60 minutes, preferably, the time of the low-temperature oxidation is 30 minutes.
[0041] The temperature of the medium-temperature oxidation is 30-40° C., preferably, the temperature of the medium-temperature oxidation is 35° C., and the time of the medium-temperature oxidation is 100-150 minutes, preferably, the time of the medium-temperature oxidation is 120 minutes.
[0042] The temperature of high temperature oxidation is 90-110° C., preferably, the temperature of high temperature oxidation is 100° C.; the time of high temperature oxidation is 10-30 minutes, preferably, the time of high temperature oxidation is 20 minutes.
[0043] Preferably, water is added during the high temperature oxidation process, and ultrapure water is the best choice. After adding water, the temperature of the high temperature oxidation no longer rises, that is, no water is added, and the amount of water added is not limited.
[0044] Preferably, the low-temperature oxidation, the medium-temperature oxidation and the high-temperature oxidation are carried out under stirring conditions; the stirring rate is 100-300 r / min (revolutions per minute), and a more preferred stirring rate is 200 r / min.
[0045] In the preparation method of graphene oxide, after cooling, the high-temperature oxidation product is further subjected to sequential removal of potassium permanganate, washing, pH adjustment and drying. Preferably, the reagent for removing potassium permanganate is an aqueous hydrogen peroxide solution, and the concentration of the aqueous hydrogen peroxide solution is 30 wt.% (weight percentage). In the process of removing potassium permanganate, the amount of the aqueous hydrogen peroxide solution is not limited. When the mixed solution of the high-temperature oxidation product and the aqueous hydrogen peroxide solution turns golden yellow, the addition of the aqueous hydrogen peroxide solution is stopped. In the present invention, the washing method is preferably centrifugal washing. There is no special limitation on the method for adjusting the pH value, and the method for adjusting the pH value commonly used in the prior art can be used, and the pH value can be adjusted to 7-8. Preferably, the drying method is freeze drying, the freeze drying temperature is -60°C to -40°C, the more preferred freeze drying temperature is -50°C to -45°C, the freeze drying time is 45-50 hours, and the more preferred freeze drying time is 48 hours.
[0046] Preferably, in the preparation method of the blue light absorber, the mass ratio of graphene oxide to hydrogen peroxide is 1g:8-12ml, and the more preferred mass ratio is 1g:10ml. Preferably, the mass ratio of graphene oxide to ultrapure water is 1g:90-110ml, and the more preferred mass ratio is 1g:100ml.
[0047] The temperature of the hydrothermal reaction in step S1 is preferably 150°C-180°C, and a more preferred hydrothermal reaction temperature is 160°C; the insulation time of the hydrothermal reaction is 90-120 minutes, and a more preferred hydrothermal reaction insulation time is 100 minutes.
[0048] Preferably, based on the mass fraction of graphene quantum dots, 0.07-0.09 parts of graphene quantum dots, the anhydrous ethanol in the blue light absorber is 110-130 parts, and more preferably the mass fraction of anhydrous ethanol is 118 parts.
[0049] Preferably, based on the mass fraction of graphene quantum dots, 0.07-0.09 parts of graphene quantum dots, 0.05-0.07 parts of aminonitrobenzene compounds in the blue light absorber, and more preferably 0.06 parts of aminonitrobenzene compounds.
[0050] Preferably, based on the mass fraction of graphene quantum dots, 0.07-0.09 parts of graphene quantum dots, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) in the blue light absorber is 1-2 parts, and the more preferred 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) is 1.2 parts; N-hydroxysuccinimide (NHS) is 0.3-0.6 parts, and the more preferred N-hydroxysuccinimide (NHS) is 0.4 parts.
[0051] The activation in step S2 is to activate the carboxyl groups on the surface of the graphene quantum dots using 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) and N-hydroxysuccinimide (NHS).
[0052] Preferably, the activation temperature in step S2 is room temperature, the activation time is 1-3 hours, and the more preferred activation time is 2 hours.
[0053] Preferably, the aminonitrobenzene compound includes 4-nitroaniline, o-nitroaniline or 4-nitro-o-phenylenediamine, and a more preferred aminonitrobenzene compound is 4-nitro-o-phenylenediamine.
[0054] Preferably, the amide reaction in step S3 is an amide reaction between the amino groups of the aminonitrobenzene compound and the activated carboxyl groups on the surface of the graphene quantum dots. The temperature of the amide reaction is 30°C-40°C, preferably 35°C, and the insulation time of the amide reaction is 22-26 hours, preferably 24 hours.
[0055] Furthermore, after the amide reaction in step S3, the product obtained by the amide reaction is cooled, dialyzed and filtered in sequence to obtain a filtrate, and freeze-dried to obtain a blue light absorber powder. The product obtained by the amide reaction is cooled to room temperature, and the dialysis bag used for dialysis is MWCO-1000 (the molecular weight cutoff of the dialysis bag is 1000 Daltons), and the dialysis time is 2-3 days; the pore size of the filter membrane for filtration is 0.22 microns, the freeze-drying temperature is -60°C to -40°C, and the more preferred freeze-drying temperature is -50°C to -45°C, the freeze-drying time is 45-50 hours, and the more preferred freeze-drying time is 48 hours.
[0056] The present invention also provides a blue light protection optical film, comprising: 0.2-1.4 parts of a blue light absorber, 9-27 parts of ultrapure water and 1-3 parts of polyvinyl alcohol; the blue light absorber is one of the blue light absorbers mentioned above.
[0057] The concentration of the blue light absorber is 0.1-0.7 wt.% (weight percentage), and the more preferred concentrations of the blue light absorber are 0.1 wt.%, 0.3 wt.%, 0.5 wt.% or 0.07 wt.%, among which the concentration of the blue light absorber is 0.07 wt.% and the effect is best.
[0058] The present invention also provides a method for preparing a blue light-proof optical protective film, comprising the following steps:
[0059] A. mixing polyvinyl alcohol and ultrapure water, and then swelling and dissolving them in sequence to obtain a polyvinyl alcohol solution;
[0060] B. mixing the polyvinyl alcohol solution and the blue light absorber to obtain a mixed material;
[0061] C. Coating the mixed material onto a glass substrate and then drying it to obtain a blue light protection optical protective film.
[0062] Preferably, the polyvinyl alcohol in step A is polyvinyl alcohol 1799 type.
[0063] Preferably, the swelling temperature in step A is room temperature, the swelling time is 0.5-1 hour, and the more preferred swelling time is 45 minutes; the dissolution temperature in step A is 90°C-110°C, the more preferred dissolution temperature is 100°C, the dissolution time is 1-3 hours, and the more preferred dissolution time is 2 hours.
[0064] Preferably, the drying temperature in step C is 60° C.-70° C., more preferably 65° C., and the drying time is 2-4 hours, more preferably 3 hours.
[0065] The thickness of the prepared anti-blue light optical protective film is 40-70 microns, and the preferred thickness of the anti-blue light optical protective film is 50-60 microns.
[0066] Example 1
[0067] The actual preparation process of the blue light absorber is as follows: 4 g of flake graphite powder (particle size of 8000 mesh) is weighed and placed in a beaker, and low-temperature reaction is carried out at 10°C for 30 minutes, then placed in an ice water bath and placed on a magnetic heating stirrer, 200 ml of 98.3% sulfuric acid is weighed, and stirred at 200 r / min (revolutions per minute) for 5 minutes to obtain a mixture; when the temperature of the mixture drops below 10°C, 24 g of potassium permanganate is weighed and slowly added to the above mixture in 3 times, and the temperature of the mixture is kept <15°C during the addition process. After the addition of potassium permanganate is completed, low-temperature oxidation is carried out at 200 r / min (revolutions per minute) and a temperature of 10°C for 30 minutes, then the ice water bath is ended, and the mixture is transferred to a constant temperature water bath at 35°C, and medium-temperature oxidation is carried out for 2 hours, then the temperature was raised from 10°C to 35°C, ultrapure water was slowly added, and high-temperature oxidation was carried out at 95°C for 20 minutes until the temperature no longer rose after the ultrapure water was added, and then it was naturally cooled to room temperature, and then 20m of a 30% aqueous hydrogen peroxide solution was added dropwise until the solution turned golden yellow, and finally centrifugation was performed to wash the solution, the pH value of the solution was adjusted to be close to 7, and after freeze-drying at -50°C for 48 hours, graphene oxide was obtained.
[0068] 1g of the above graphene oxide, 100ml of ultrapure water and 10ml of hydrogen peroxide aqueous solution were weighed and mixed and ultrasonicated until the graphene oxide was uniformly dispersed in the ultrapure water to obtain a dispersion. The dispersion was then placed in a tetrafluoroethylene liner of a 150ml reactor, placed in an oven at 160°C for hydrothermal reaction for 100 minutes, cooled to room temperature, filtered with filter paper to remove the precipitate, and the obtained filtrate was dialyzed with a MWCO-1000 dialysis bag for 2 days, and the liquid in the dialysis bag was filtered with a 0.22 micron filter head. The obtained solution was refrigerated and dried at -50°C for 48 hours to obtain graphene quantum dots (GQDs).
[0069] 0.075 g of graphene quantum dots (GQDs) were weighed and dissolved in 150 ml of anhydrous ethanol, and 1.2 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) and 0.4 g of N-hydroxysuccinimide (NHS) were added for activation, stirred at room temperature for 2 hours, and then the activated graphene quantum dot reaction solution was reacted with 0.05 g of 4-nitroaniline (p-NP) at 35°C for 24 hours. After the reaction was completed, it was cooled to room temperature, and then dialyzed with a MWCO-1000 dialysis bag for 2 days. The liquid in the dialysis bag was filtered with a 0.22 micron filter head, and the filtrate was lyophilized at -50°C for 48 hours to obtain the blue light absorber, which was recorded as 4-nitroaniline-graphene quantum dots (p-NP-GQDs).
[0070] Example 2
[0071] The difference between this embodiment and embodiment 1 is that "4-nitroaniline (p-NP)" is replaced by "o-nitroaniline (o-NP)" to obtain the blue light absorber, which is recorded as o-nitroaniline-graphene quantum dots (o-NP-GQDs).
[0072] Example 3
[0073] The difference between this embodiment and embodiment 1 is that "4-nitroaniline (p-NP)" is replaced by "4-nitro-o-phenylenediamine (DNP)" to obtain the blue light absorber, which is recorded as 4-nitro-o-phenylenediamine-graphene quantum dots (DNP-GQDs).
[0074] The UV-visible absorption curves of the p-NP-GQDs, o-NP-GQDs and DNP-GQDs prepared in Examples 1-3 are as follows: Figure 1 As shown, Figure 1 The horizontal coordinate Wavelength refers to the wavelength, and its unit is nanometers. The vertical coordinate Absorption (au) refers to the absorbance. The gray curve represents the test curve of the conventional blue light absorber (graphene quantum dots (GQDs)), the red curve represents the test curve of the blue light absorber with 4-nitroaniline (4-nitroaniline-graphene quantum dots (p-NP-GQDs)), the blue curve represents the test curve of the blue light absorber with o-nitroaniline (o-nitroaniline-graphene quantum dots (o-NP-GQDs)), and the blue curve represents the test curve of the blue light absorber with 4-nitro-o-phenylenediamine (4-nitro-o-phenylenediamine-graphene quantum dots (DNP-GQDs)). Figure 1 It can be seen that p-NP-GQDs, o-NP-GQDs and DNP-GQDs all have a certain effect in blocking harmful blue light, among which DNP-GQDs has the best effect in blocking harmful blue light.
[0075] Application Example 1
[0076] Weigh 9 ml of ultrapure water and place it in a beaker, swell 1 g of polyvinyl alcohol 1799 at room temperature for 45 minutes, then heat to 95°C at a rate of 10°C / min (degrees per minute), dissolve for 2 hours and then naturally cool to room temperature to obtain a polyvinyl alcohol solution. Mix 0.01 g of 4-nitroaniline-graphene quantum dots (p-NP-GQDs) with the polyvinyl alcohol solution to obtain a 0.1 wt% (weight percentage) mixture (4-nitroaniline-graphene quantum dots and polyvinyl alcohol mixture), coat the mixture on a glass substrate, and dry at 65°C for 3 hours to obtain a 0.1 wt% (weight percentage) p-NP-GQDs / PVA anti-blue light optical protective film with a thickness of 50-60 microns.
[0077] Application Example 2
[0078] The difference between this application example and application example 1 is that "0.01 g p-NP-GQDs" is replaced with "0.03 g p-NP-GQDs", and the anti-blue light optical protective film is obtained, which is recorded as 0.3 wt% p-NP-GQDs / PVA.
[0079] Application Example 3
[0080] The difference between this application example and application example 1 is that "0.01 g p-NP-GQDs" is replaced with "0.05 g p-NP-GQDs" to obtain the anti-blue light optical protective film, which is recorded as 0.5 wt% p-NP-GQDs / PVA.
[0081] Application Example 4
[0082] The difference between this application example and application example 1 is that "0.01 g p-NP-GQDs" is replaced with "0.07 g p-NP-GQDs" to obtain the anti-blue light optical protective film, which is recorded as 0.7 wt% p-NP-GQDs / PVA.
[0083] The UV-visible light transmittance test curve of the anti-blue light optical protective film obtained in Application Examples 1-4 is as follows: Figure 2 shown. Figure 2 The horizontal coordinate Wacelength refers to the wavelength, and its unit is nanometers. The vertical coordinate Transmittance refers to the transmittance. The gray curve represents the test curve of ordinary polyvinyl alcohol (PVA) anti-blue light optical protective film, the red curve represents the test curve of the composite coating composed of 0.1 wt% 4-nitroaniline-graphene quantum dots and polyvinyl alcohol (0.1 wt% p-NP-GQDs / PVA), the blue curve represents the test curve of the composite coating composed of 0.3 wt% 4-nitroaniline-graphene quantum dots and polyvinyl alcohol (0.3 wt% p-NP-GQDs / PVA), the green curve represents the test curve of the composite coating composed of 0.5 wt% 4-nitroaniline-graphene quantum dots and polyvinyl alcohol (0.5 wt% p-NP-GQDs / PVA), and the purple curve represents the test curve of the composite coating composed of 0.7 wt% 4-nitroaniline-graphene quantum dots and polyvinyl alcohol (0.7 wt%p-NP-GQDs / PVA) test curve.
[0084] from Figure 2It can be seen that the transmittance of the composite coatings (0.1 wt% p-NP-GQDs / PVA, 0.3 wt% p-NP-GQDs / PVA, 0.5 wt% p-NP-GQDs / PVA and 0.7 wt% p-NP-GQDs / PVA) in the range of 400-460 nm gradually decreases with the increase of thickness, which also shows that the composite coating has a certain harmful blue light blocking effect.
[0085] Application Example 5
[0086] The difference between this application example and application example 1 is that "0.01 g p-NP-GQDs" is replaced by "0.01 g o-NP-GQDs" to obtain the anti-blue light optical protective film, which is recorded as 0.1 wt% o-NP-GQDs / PVA.
[0087] Application Example 6
[0088] The difference between this application example and application example 1 is that "0.01 g p-NP-GQDs" is replaced by "0.03 g o-NP-GQDs" to obtain the anti-blue light optical protective film, which is recorded as 0.3 wt% o-NP-GQDs / PVA.
[0089] Application Example 7
[0090] The difference between this application example and application example 1 is that "0.01 g p-NP-GQDs" is replaced by "0.05 g o-NP-GQDs" to obtain the anti-blue light optical protective film, which is recorded as 0.5 wt% o-NP-GQDs / PVA.
[0091] Application Example 8
[0092] The difference between this application example and application example 1 is that "0.01 g p-NP-GQDs" is replaced by "0.07 g o-NP-GQDs" to obtain the anti-blue light optical protective film, which is recorded as 0.7 wt% o-NP-GQDs / PVA.
[0093] The UV-visible light transmittance test curve of the anti-blue light optical protective film obtained in Application Examples 5-8 is as follows: Figure 3 shown. Figure 3The horizontal coordinate Wacelength refers to the wavelength, and its unit is nanometers. The vertical coordinate Transmittance refers to the transmittance. The gray curve represents the test curve of ordinary polyvinyl alcohol (PVA) anti-blue light optical protective film, the red curve represents the test curve of the composite coating composed of 0.1 wt% o-nitroaniline-graphene quantum dots and polyvinyl alcohol (0.1 wt%o-NP-GQDs / PVA), the blue curve represents the test curve of the composite coating composed of 0.3 wt% o-nitroaniline-graphene quantum dots and polyvinyl alcohol (0.3 wt%o-NP-GQDs / PVA), the green curve represents the test curve of the composite coating composed of 0.5 wt% o-nitroaniline-graphene quantum dots and polyvinyl alcohol (0.5 wt%o-NP-GQDs / PVA), and the purple curve represents the test curve of the composite coating composed of 0.7 wt% o-nitroaniline-graphene quantum dots and polyvinyl alcohol (0.7 wt%o-NP-GQDs / PVA) test curve.
[0094] from Figure 3 It can be seen that the transmittance of the composite coatings (0.1 wt% o-NP-GQDs / PVA, 0.3 wt% o-NP-GQDs / PVA, 0.5 wt% o-NP-GQDs / PVA and 0.7 wt% o-NP-GQDs / PVA) in the range of 400-460 nm gradually decreases with the increase of thickness, which also shows that the composite coating has a certain harmful blue light blocking effect.
[0095] Application Example 9
[0096] The difference between this application example and application example 1 is that "0.01 g p-NP-GQDs" is replaced with "0.01 g DNP-GQDs" to obtain the anti-blue light optical protective film, which is recorded as 0.1 wt% DNP-GQDs / PVA.
[0097] Application Example 10
[0098] The difference between this application example and application example 1 is that "0.01 g p-NP-GQDs" is replaced with "0.03 g DNP-GQDs" to obtain the anti-blue light optical protective film, which is recorded as 0.3 wt% DNP-GQDs / PVA.
[0099] Application Example 11
[0100] The difference between this application example and application example 1 is that "0.01 g p-NP-GQDs" is replaced with "0.05 g DNP-GQDs" to obtain the anti-blue light optical protective film, which is recorded as 0.5 wt% DNP-GQDs / PVA.
[0101] Application Example 12
[0102] The difference between this application example and application example 1 is that "0.01 g p-NP-GQDs" is replaced with "0.07 g DNP-GQDs" to obtain the anti-blue light optical protective film, which is recorded as 0.7 wt% DNP-GQDs / PVA.
[0103] The UV-visible light transmittance test curves of the anti-blue light optical protective films obtained in Application Examples 9-12 are as follows: Figure 4 shown. Figure 4 The horizontal coordinate Wacelength refers to the wavelength, and its unit is nanometers. The vertical coordinate Transmittance refers to the transmittance. The gray curve represents the test curve of ordinary polyvinyl alcohol (PVA) anti-blue light optical protective film, the red curve represents the test curve of the composite coating composed of 0.1 wt% 4-nitro-o-phenylenediamine-graphene quantum dots and polyvinyl alcohol (0.1 wt% DNP-GQDs / PVA), the blue curve represents the test curve of the composite coating composed of 0.3 wt% 4-nitro-o-phenylenediamine-graphene quantum dots and polyvinyl alcohol (0.3 wt% DNP-GQDs / PVA), the green curve represents the test curve of the composite coating composed of 0.5 wt% 4-nitro-o-phenylenediamine-graphene quantum dots and polyvinyl alcohol (0.5 wt% DNP-GQDs / PVA), and the purple curve represents the test curve of the composite coating composed of 0.7 wt% 4-nitro-o-phenylenediamine-graphene quantum dots and polyvinyl alcohol (0.7 wt%DNP-GQDs / PVA) test curve.
[0104] from Figure 4 It can be seen that the transmittance of the composite coatings (0.1 wt% DNP-GQDs / PVA, 0.3 wt% DNP-GQDs / PVA, 0.5 wt% DNP-GQDs / PVA and 0.7 wt% DNP-GQDs / PVA) in the range of 400-460 nm gradually decreases with the increase of thickness, which also shows that the composite coating has a good harmful blue light blocking effect.
[0105] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. An anti-blue light optical protective film, characterized in that: The composition comprises, by weight, 0.2-1.4 parts of a blue light absorber, 9-27 parts of ultrapure water and 1-3 parts of polyvinyl alcohol; The blue light absorber is composed of 0.07-0.09 parts of graphene quantum dots, 110-130 parts of anhydrous ethanol, 0.05-0.07 parts of aminonitrobenzene compounds, 1-2 parts of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.3-0.6 parts of N-hydroxysuccinimide in parts by mass; The blue light absorber is prepared by the following method: The following steps are involved: S1, mixing graphene oxide, hydrogen peroxide and ultrapure water, and subjecting the obtained dispersion to a hydrothermal reaction to obtain graphene quantum dots; the temperature of the hydrothermal reaction in step S1 is 150° C.-180° C., and the holding time of the hydrothermal reaction is 90-120 minutes; S2, mixing graphene quantum dots, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide and ethanol, and then activating to obtain a graphene quantum dot reaction solution; the activation temperature in step S2 is room temperature, and the activation time is 1-3 hours; S3, mixing the graphene quantum dot reaction solution and the aminonitrobenzene compound, and then performing an amide reaction to obtain a blue light absorber; the temperature of the amide reaction in step S3 is 30° C.-40° C., and the insulation time of the amide reaction is 22-26 hours.
2. The anti-blue light optical protective film according to claim 1, characterized in that: The concentration of the blue light absorber is 0.1-0.7 wt.%.
3. The anti-blue light optical protective film according to claim 1, characterized in that: The aminonitrobenzene compounds include 4-nitroaniline, o-nitroaniline or 4-nitro-o-phenylenediamine.
4. A method for preparing the anti-blue light optical protective film according to claim 1, characterized in that: The following steps are involved: A. mixing polyvinyl alcohol and ultrapure water, and then swelling and dissolving them in sequence to obtain a polyvinyl alcohol solution; B. mixing the polyvinyl alcohol solution and the blue light absorber to obtain a mixed material; C. Coating the mixed material onto a glass substrate and then drying it to obtain a blue light protection optical protective film.
5. The method for preparing a blue light protection optical protective film according to claim 4, characterized in that: The swelling temperature in step A is 20° C.-30° C., and the swelling time is 0.5-1 hour; the dissolution temperature in step A is 90° C.-110° C., and the dissolution time is 1-3 hours.
6. The method for preparing a blue light protection optical protective film according to claim 4, characterized in that: The drying temperature in step C is 60° C.-70° C., and the drying time is 2-4 hours.
Citation Information
Patent Citations
Preparation method and application of nano magnetic polylysine / (graphene-carbon nano tube) biological adsorption material
CN106076271A
Modified graphene quantum dot and preparation method thereof, graphene quantum dot / light-cured resin composite material and polaroid
CN115849351A
Cited By
Optical composite film for preventing and controlling myopia and preparation method thereof
CN120214982A